SOSIALISASI PENGGUNAAN PAKAIAN SYAR’I TERHADAP SISWA-SISWI MELALUI PENDEKATAN PERSUASIF DI MADRASAH ALIYAH PERSIAPAN NEGERI BESITANG - Wahyu Ziaulhaq; M. Idris (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
This study describes the socialization of the use of syar'i clothing to students through a persuasive approach in the preparatory madrasah in Besitang. The purpose of this study is to educate students and readers to always wear clothes that are based on Islamic religious guidance. This type of research is a qualitative research that seeks to explain social phenomena that are developing in the current mass, from the results of this study it was found that: the teacher council always provides education to students so that they cover their aurat when they are in the madrasa environment or in the community by using humanist and persuasive language, it takes the role of parents of students to always give advice to their children so that they always uphold dress etiquette, the teacher council will give sanctions to students if they violate dress procedures when in the madrasa environment.